2020
DOI: 10.1002/ctm2.182
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro activation of dormant primordial follicles by EGF treatment in mouse and human

Abstract: In the mammalian ovaries, dormant primordial follicles represent the reproductive reserve of individual females. Recently, stimulating the activation of primordial follicles in vitro has been practiced, making the utilization of those dormant follicles to treat female infertility possible. However, there are still lacks of effective upstream molecule and strategy to elevate follicle activation in vivo. In the current study, we revealed that growth factor EGF improved a transiently primordial follicle activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Notably, native hepatocytes exhibited a marked increase in Ki67 + expression in the liver following HACY administration, thus showing a potential benefit by stimulating hepatic regeneration in the host. Other studies have shown that in vivo EGF treatment can reestablish the balance between growing follicles and dormant follicles following an acute change of ovarian microenvironment 25 . Similarly, the internal administration of HACY may reestablish a balance favoring liver regeneration, thus providing a clinically effective approach for the treatment of chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, native hepatocytes exhibited a marked increase in Ki67 + expression in the liver following HACY administration, thus showing a potential benefit by stimulating hepatic regeneration in the host. Other studies have shown that in vivo EGF treatment can reestablish the balance between growing follicles and dormant follicles following an acute change of ovarian microenvironment 25 . Similarly, the internal administration of HACY may reestablish a balance favoring liver regeneration, thus providing a clinically effective approach for the treatment of chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…During the process, the decline of HDAC6 may be transient because the levels of HDAC6 elevates in primary follicles soon. According to previous studies, short-term activation treatment with one of the activators of either AKT, CDC42, or SIRT1 promotes the activation of mouse primordial follicles in vitro 9 , 11 , 12 , 17 , 31 , 32 . Therefore, the transition of primordial follicles from the dormant state to the activated state may be a very short process.…”
Section: Discussionmentioning
confidence: 94%
“…The importance of PI3K/Akt pathway in primordial follicle activation has been well-established [ 6 , 7 , 8 , 9 ]. This pathway has been shown to be modulated by numerous intraovarian growth factors including Kit ligand (KL), insulin-like growth factor I, platelet-derived growth factor, and EGF [ 7 , 38 , 39 ]. On the other hand, phosphatase and tensin homolog deleted on chromosome 10 (PTEN), a lipid phosphatase converting phosphatidylinositol-3,4,5-triphosphate (PIP3) back to phosphatidylinositol biphosphate (PIP2), negatively regulates the PI3K/Akt pathway [ 6 ].…”
Section: The Pi3k/akt Pathway—the Major Pathway Governing the Actimentioning
confidence: 99%
“…The recent experiment suggested that EGF could be an alternative agent to activate the primordial follicle through elevating CDC42-PI3K signaling and PI3K/Akt pathway in both murine and human ovarian tissue. After treatment of mouse ovaries with EGF by in vitro culture together with in vivo topical administration of EGF dissolved in the Matrigel into ovarian bursa, the histological results demonstrated an increase in the percentage of growing follicles in EGF-treated ovaries compared to controls [ 39 ]. In human tissues, similar results were observed by culturing ovarian cortical fragments with EGF [ 39 ].…”
Section: The Pi3k/akt Pathway—the Major Pathway Governing the Actimentioning
confidence: 99%